Microscopic Study of Basement Membrane in Oesophagus of Human Body with Comparative Study of Laboratory Animals - V.S. Shirol1, S.S. Goudar2; R. S. Humbarwadi3, Suresh P. Desai1, (Recent Research in Science and Technology, 2011)
The basement membrane is a term, originally given to a layer of variable thickness and distinction found at the basal surfaces of epithelia Michel Ross, (1989). Since the layer was positioned immediately below the bases of the epithelial cells, this layer was termed basement membrane. Basement membrane serves as a selective filtration barrier to substances, moving between the interstitium and the parenchymal cells. Pierce, Midgley and Ram (1964), were the first to classify the basement membrane under two structural headings: a) Homogeneous Lamella, (b) Fibrillar Lamella.Ã‚Â Arthur Ham (1979), described the basement membrane as a thick structure less membrane just below the tracheal epithelium. It was later believed that all epithelial cells rested on such a membrane although generally less thick than that in trachea. This extracellular supporting layer has been interpreted by William Bloom and Don Fawcett (1968), as a condensation of the ground substance of the connective tissue, at its interface with the epithelium. The basement membranes are laminae of dense amorphous material, which vary in thickness and are associated with many types of cells, embedded in or adjacent to connective tissue eg. Schwan cells, capillary endothelium and epithelia in general, Kefalides N.A. (1973). In some situations the basement membrane may be particularly thick easier to investigate, as in the glomerular membrane and so, cornea and deep to the mucous lining of trachea. It is believed that the epithelia secrete a special variety of cell coat or g1ycocalyx along their basal surfaces where they border underlying connective tissue. This material consists of mucoprotein matrix within which very fine matted filaments of a special type of collagen are embedded. This mat is termed the basal lamina. Bailey (1978). A similarly disposed layer around the basal surface of kidney tubules is almost entirely composed of basal lamina. In other locations such as ureter, where beneath the transitional epithelium, the basement membrane is so thin as to be un-resolvable by light microscope. The basement membrane is often difficult to see in routine Haematoxylin and Eosin (H & E) preparation, but can clearly be demonstrated by staining with Periodic Acid Schiff (PAS) or with silver impregnation methods. Basement membrane then appears as a thin continuous layer applied to the base of the epithelium. Basement membrane is not a single structure, but has two or more distinct components that are not resolved as such, with light microscopy. However, electron microscope showed that the deeper part of the basement membrane was actually composed of a matted network of reticular fibres. The basal lamina is usually about 80 rim thick and consists of fibrillar layer lamina densa (20 to 50 nm wide) and lamina lucida, intervening between adjacent cell membrane and lamina desna. The lamina lucida shows granular or fibrillar features, regularly spaced. The lamina densa is composed chiefly of a delicate network of type IV collagen fibrils andÃ‚Â heparan sulphate proteoglycan. Lamina lucida has been shown to contain laminin, fibronectin and various proteo81ycans. These three molecules may be important in adhesions of cells to the basal lamina and adhesion of the basal lamina to the connective tissue matrix. Outside the basal lamina are small fascicles of unit fibrils of collagen and reticular fibres, embedded in the amorphous protein polysaccharide ground substance. All these components which, include basal lamina, reticular fibres and ground substance contribute in the formation of basement membrane. The chemical composition of basement membrane is 90% protein, 8% carbohydrates and 2% lipids. There are approximately equal amounts of collagen like and non-collagen proteins, the latter being g1ycoproteins, containing glucose, galactose, mannose, hexosamine and some sialic acid. This is amply demonstrated in their staining reactions. The reticular fibres are mainly responsible for its impregnation with silver’ salts and appear black. While the Periodic-Acid-Schiff reaction (PAS) involves the polysaccharides of the basal lamina and the ground substance, and appear magenta. Chemical studies of isolated basal lamina from the kidney, indicate that, their main structural component is a form of a collagen. There is now considerable evidence that this layer is a product of the overlying epithelium and not a condensation of the underlying connective tissue ground substance. However, this is still disputed [William Bloom and Don Fawcett (1968)]. Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â The reticular fibres and their associated polysaccharide matrix are mainly the products of connective tissue fibroblasts. The basal lamina was found to be always following the contours of the basal surface of the epithelium. Basement membrane provides attachment for the epithelium to the underlying connective tissue and to influence the differentiation and proliferation of the epitheial cells that contact it. There has been much interest in the role of basement membrane in regeneration of the peripheral nerves after injury. Here basal lamina components appear to be involved in guiding outgrowths of axon and the re-establishment of fibre continuity. Besides, this knowledge is being increasingly applied to the clinical field. In diabetes there is a great prominence of the capillaries due to thickening and reduplication of the basement membrane, the fibrillar structure of which is markedly exaggerated. In most of these situations the individual layers of basement membrane have probably been deposited there, by now cell generations, give an indication of the number of cell generations which have occurred at that particular site, like rings on cross section of tree trunks. One of the prominent features of alveolar reaction to injury, is thickness of alveolar septum caused by expansion of interstitium leading to an increase in Air- Blood-gas exchange distance. In acute alveolar injury, in which the interstitial edema is prominent, there appears to be no separation of interstitial edema is prominent, there appears to be no separation of composite basal laminae, although the thick part of the alveolar septum is greatly expanded by edema field. In chronic alveolar injury, the interstitial reaction is dominated by fibrosis. The hyperplastic granular pneumocytes are frequently seen resting on the basal lamina facing connective tissue. The significance of these changes and their specific effect on tissue function is still unclear. Hence an attempt has been made to study the structure of the basement membrane under light microscope, in selected organs of human and laboratory animate be staining with special techniques and compare the results.